Alternative Splicing of MAPKs in the Regulation of Signaling Specificity - Galia Maik-Rachline; Inbal Wortzel; Rony Seger (Cells, 2021)
The mitogen-activated protein kinase (MAPK) cascades transmit signals from extracellular stimuli to a variety of distinct cellular processes. The MAPKKs in each cascade specifically phosphorylate and activate their cognate MAPKs, indicating that this step funnels various signals into a seemingly linear pathway. Still, the effects of these cascades vary significantly, depending on the identity of the extracellular signals, which gives rise to proper outcomes. Therefore, it is clear that the specificity of the signals transmitted through the cascades is tightly regulated in order to secure the desired cell fate. Indeed, many regulatory components or processes that extend the specificity of the cascades have been identified. Here, we focus on a less discussed mechanism, that is, the role of distinct components in each tier of the cascade in extending the signaling specificity. We cover the role of distinct genes, and the alternatively spliced isoforms of MAPKKs and MAPKs, in the signaling specificity. The alternatively spliced MEK1b and ERK1c, which form an independent signaling route, are used as the main example. Unlike MEK1/2 and ERK1/2, this route’s functions are limited, including mainly the regulation of mitotic Golgi fragmentation. The unique roles of the alternatively spliced isoforms indicate that these components play an essential role in determining the proper cell fate in response to distinct stimulations.